Are there gender differences in family trajectories by education in Finland? - Marika Jalovaara; Anette Eva Fasang (Demographic Research, 2015)
[Background:] Previous studies suggest that in some countries socioeconomic differences in family formation are highly gendered, whereas gender-neutral patterns are reported in other countries. Most previous studies focus on single events and therefore it is unclear how the gender differences and neutralities in family transitions combine into variation in longer family-formation trajectories. [Objective:] We explore how family trajectories vary by educational attainment and gender. The research asks whether there are gender differences in family trajectories by education. We focus on the trajectories of women and men in Finland between the ages of 18 and 39, and on the 1969 and 1970 birth cohorts. The trajectories consist of states entered via the formation and dissolution of cohabitation and marriage and the birth of the first child. [Methods:] We give a sequence representation of Finnish register data comprising monthly histories of union dynamics and childbearing. We focus on the number and order of family states. [Results:] We find notable differences in family trajectories by educational attainment; however, the gender differences in the trajectories within educational groups are negligible. For instance, the proportion of never-partnered and childless at age 39 is largest among those with low education, regardless of gender. Further, at age 39, highly educated women and men are most likely to live in the same union in which they became first-time parents. [Contribution:] This study adds to previous literature by showing that in an egalitarian Nordic welfare state, longitudinal family-formation trajectories are highly stratified by education but remarkably gender-neutral.
Keywords: 300; childbearing; cohabitation; education; family trajectories; Finland; gender; marriage; sequence analysis